2003
DOI: 10.1034/j.1601-5215.2003.00039.x
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of Capgras syndrome in a university hospital setting

Abstract: The results of this study indicate that Capgras syndrome is not a rare syndrome, and commonly occurs during the course of either functional or organic psychotic illness. Age seems to be an important predicting factor for the etiology of psychosis underlying Capgras syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
2

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 25 publications
0
8
0
2
Order By: Relevance
“…The keyword 'Capgras' was then used in a formal search of free-text record fields, retrieving records from 187 patients. Previous case-identification studies have tended to select cases based on informal labels used by consulting clinicians, 11 or single-rater review of case notes using a brief description of the delusion (see Tamam et al 12 ). In this study, the 187 anonymised records were subsequently independently rated by a psychiatrist and clinical psychologist for the likely presence of Capgras delusion using the structured classification system described in Fig.…”
Section: Case Selectionmentioning
confidence: 99%
“…The keyword 'Capgras' was then used in a formal search of free-text record fields, retrieving records from 187 patients. Previous case-identification studies have tended to select cases based on informal labels used by consulting clinicians, 11 or single-rater review of case notes using a brief description of the delusion (see Tamam et al 12 ). In this study, the 187 anonymised records were subsequently independently rated by a psychiatrist and clinical psychologist for the likely presence of Capgras delusion using the structured classification system described in Fig.…”
Section: Case Selectionmentioning
confidence: 99%
“…A study conducted in an acute psychiatric service found that the CS rate was 2.5%, 24 and in another study that evaluated the previous 5 years of patients’ records in a university hospital, the rate was 1.3%. 25 This syndrome can affect both genders at all ages; however, some authors found higher prevalence in females than in males, with a 2:1 ratio. 26 Few reports have described this syndrome during childhood.…”
Section: Introductionmentioning
confidence: 99%
“…Signer reviewed 750 cases with DMSs, out of which 200 cases had an organic contributor (8). But as mentioned in the Introduction, two patients of 920 cases presented with an organic etiology underlying Capgras syndrome in Taman's review (3). Capgras syndrome was reported as a part of early post-head injury delirium (9).…”
Section: Resultsmentioning
confidence: 99%
“…Two patients presented with an organic etiology underlying Capgras syndrome. They concluded that Capgras syndrome is not a rare syndrome (3).…”
Section: Introductionmentioning
confidence: 99%